2012
DOI: 10.1089/acm.2011.0390
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Progressive Relaxation Exercises on Fatigue and Sleep Quality in Patients with Multiple Sclerosis

Abstract: Background and objectives: Fatigue and sleep problems are very commonly observed in patients with multiple sclerosis (MS). The Progressive Muscle Relaxation Technique (PMRT), used as one of the alternative methods in recent years, is reported to have benefits such as facilitating sleep and reducing sensitivity against fatigue. This research was conducted to investigate the effect of PMRT on fatigue and sleep quality in patients with MS. Setting and design: This research was performed as a single-group pretest/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 27 publications
2
60
0
5
Order By: Relevance
“…This is the first study in MS using COPM as a (primary) outcome, but most of the energy conservation programs and relaxation techniques showed a reduction of fatigue (Dayapoğlu and Tan, 2012;Blikman et al, 2013). Energy conservation interventions all used a group format and were compared with wait list controls receiving no intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study in MS using COPM as a (primary) outcome, but most of the energy conservation programs and relaxation techniques showed a reduction of fatigue (Dayapoğlu and Tan, 2012;Blikman et al, 2013). Energy conservation interventions all used a group format and were compared with wait list controls receiving no intervention.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a growing number of individuals have turned to mind-body therapies-a specific exercise regimen including yoga, mediation, relaxation techniques, breath work, visual imagery, hypnotherapy, and biofeedback-to manage symptoms of MS. [27][28][29][30][31][32][33] For example, Yadav and colleagues 32 conducted a survey with 1110 patients with MS. Thirty-two percent reported both highly perceived psychological and physical benefits to using mind-body modalities, such as yoga, meditation, relaxation techniques, and breathing. In another study, Nayek et al 30 gathered data from 11,600 individuals with MS and found that 57.1% of the responding sample had used at least one form of complementary and alternative medicine (CAM), citing a general preference for alternative mind-body therapies.…”
Section: Mind-body Therapies For Msmentioning
confidence: 99%
“…It is intended to help individuals calm down, and fall asleep easily. PMR is a basic relaxation technique that is easy to learn (Dayapoğlu, ; Yung, Fung, Chan, & Lau, ). It comprises of deliberate contraction and relaxation of a group of large muscles in the human body.…”
Section: Introductionmentioning
confidence: 99%